Ablation of PI3K-p110alpha Impairs Maternal Metabolic Adaptations to Pregnancy - Lopez-Tello, Jorge; Salazar-Petres, Esteban; Webb, Liam; Fowden, Abigail L.; Sferruzzi-Perri, Amanda N. (Frontiers in Cell and Developmental Biology, 2022)
Pregnancy requires adaptations in maternal metabolism to support fetal growth. The phosphoinositol-3-kinase (PI3K) signalling pathway controls multiple biological processes and defects in this pathway are linked to metabolic disorders including insulin resistance and glucose intolerance in non-pregnant animals. However, relatively little is known about the contribution of PI3K signalling to the maternal metabolic adaptations during pregnancy. Using mice with partial inactivation of the PI3K isoform, p110α (due to a heterozygous dominant negative mutation; Pik3ca-D933A), the effects of impaired PI3K-p110α signalling on glucose and insulin handling were examined in the pregnant and non-pregnant states and related to the morphological, molecular, and mitochondrial changes in key metabolic organs. The results show that non-pregnant mice lacking PI3K-p110α are glucose intolerant but exhibit compensatory increases in pancreatic glucose-stimulated insulin release and adipose tissue mitochondrial respiratory capacity and fatty acid oxidation. However, in pregnancy, mutant mice failed to show the normal increment in glucose intolerance and pancreatic β-cell mass observed in wild-type pregnant dams and exhibited further enhanced adipose tissue mitochondrial respiratory capacity. These maladaptations in pregnant mutant mice were associated with fetal growth restriction. Hence, PI3K-p110α is a key regulator of metabolic adaptations that support fetal growth during normal pregnancy.